Influencing the Relationship between Job Clarity and Turnover Intention through User Training During Enterprise System Implementation - Brattin, Rick L.; Davis, Joshua M.; Brahnam, Sheryl (Information Management and Business Review, 2019)
Enterprise system (ES) implementations introduce pervasive and disruptive change to organizations. End-users struggling to cope with such change often develop an internal self-preservation narrative that, if not managed, can lead to employee turnover. Turnover is a visibly-assertive response to ES implementations that has lasting negative effects on organizations. The job role literature suggests that an individual’s intention to leave an organization is greater when they lack clarity concerning their own work tasks and their role in achieving broader organizational goals. These clarity perceptions evolve during ES implementations as individuals become aware that their existing job context is no longer relevant to the post-implementation organization. It seems likely that the strength of relationship between job clarity and turnover intention will also evolve during this time. Accordingly, this study uses PLS-SEM multi-group analysis to examine changes in this relationship during an ES implementation at a Fortune 100 manufacturer and finds a significant increase in the influence of job clarity deficiencies on turnover intention following end-user training. These results suggest that ES implementation teams should focus their efforts on building job clarity of the post-implementation work context.